Tecnologías dominantes difusión de innovaciones y espacios tecnológicos - Legna, Carlos (Revista EURE - Revista de Estudios Urbano Regionales, 1996)
This article centres its attention on the study of the links between the transformations in the economic International order and the forces that have modeled the territory organization. The main lines of what we might call the Í€œTerritorial ParadigmÍ€ of the 90Í€™s are deduced. According to it, in the present order, it is strengthened the importance of the local culture, its capacity to cause the Í€œTo know how to do itÍ€ circulate: it is favoured the professionalism, the technical culture and the Í€œdepositsÍ€ of qualification of the human resources. This all means a revolution of the Industrial Districts, which are simultaneously strengthened with new ways of vinculation among firms, that make the networks between agents and Districts stronger. The qualified services from the new structures of these networks and play a relevant role in the internalization and space organization processes. Its concentration on certain privileged areas, combined with the fact that every regional society has its own course of generation and incorporation of innovations, constitute a powerful force that impels the unequal technological development of the spaces. From the strategic point of view particularly for the undeveloped region, this means at least these challenges: How to increase the technological level and how to develop an innovative course in order to insert the region dynamically in the present order.